Copper salt-catalyzed formation of a novel series of triazole–spirodienone conjugates with potent anticancer activity. Issue 16 (30th January 2017) - Gu, Linghui; Wang, Peng; Zhong, Qiu; Deng, Yuxing; Xie, Jiangping; Liu, Fei; Xiao, Fan; Zheng, Shilong; Chen, Yue; Wang, Guangdi; He, Ling
Abstract : Copper salt-catalyzed oxidative amination resulted in the formation of a novel series of triazole–spirodienone conjugates, 4-triazolyl-1-oxa-4-azaspiro[4, 5]deca-6, 9-dien-3, 8-diones and 4-triazolyl-1-oxa-4-azaspiro[4, 5]deca-6, 9-dien-8-ones. Abstract : Copper salt-catalyzed oxidative amination resulted in the formation of a novel series of triazole–spirodienone conjugates, 4-triazolyl-1-oxa-4-azaspiro[4, 5]deca-6, 9-dien-3, 8-diones and 4-triazolyl-1-oxa-4-azaspiro[4, 5]deca-6, 9-dien-8-ones. A single crystal of compound1p among them was grown and analyzed by X-ray crystallography. These compounds were evaluated for their antiproliferative activities against MDA-MB-231, HeLa, A549 and MCF-7 cell lines. Most of them showed moderate to high anticancer potency in the four cancer cell lines. The discovery of the triazole–spirodienone conjugates as cytotoxic agents against cancer cells may open up a new field in which these novel small molecules could be further explored as promising anticancer agents.